Relevance Of Students Competencies and Health Information in Medical Records at The Level with The Minister of Health Regulation Number 312 Of 2020 - Zulfahmi Zulfahmi; Oriza Sativa; Putri Farrah Diba (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
Universities are expected to provide graduates whose skills correspond with professional and regulatory requirements. In the domain of Medical Records and Health Information (PMIK), competency standards are officially governed by Minister of Health Regulation No. 312 of 2020, which establishes a criterion for service quality and professional efficacy. This study seeks to evaluate the correspondence between the abilities of final-year students in the 2024–2025 Medical Records and Health Information (RMIK) program at STIKes Sihat Beurata Banda Aceh and the established national criteria.A descriptive quantitative approach was utilised, encompassing all 69 final-year students via a complete sample method. The demographic profile reveals that the majority of respondents were 20 years old (52%) and primarily female (70%). The comprehensive competency evaluation indicates that the majority of students are classified as